Thermoluminescence and Mechanoluminescence studies of (Cd0.95 Zn0.05)S: Ag doped phosphor - Sao, S K; Brahme, N; Bisen, D P; Sharma, R; Tiwari, G; Tigga, S; Chandrakar, P; Tamrakar, R (Recent Research in Science and Technology, 2012)
Through the execution of experimental investigation, mechanoluminescence of (Cd,Zn)S: Ag phosphor was studied which is synthesized by solid state reaction. In the observation, the peak value of ML depends on different concentration. It is seen that ML intensity increases with Ag ion concentration in (Cd, Zn)S phosphor. The peak value of TL depends on the different UV-irradiation time. It is seen that as UV-irradiation exposure increases the TL intensity also increases.